2020
DOI: 10.1155/2020/9191505
|View full text |Cite
|
Sign up to set email alerts
|

The Use of SenseWear Armband for Assessment of Daily Energy Expenditure and the Relation to Body Fat Distribution and Nutritional Intake in Lean Women with Polycystic Ovary Syndrome

Abstract: Objective. To evaluate nutritional intake, energy expenditure, and segmental body composition in lean women with polycystic ovary syndrome (PCOS) and compare them with age- and body mass index- (BMI-) matched control women. Methods. 32 nonobese patients with PCOS and 31 age- and BMI-matched healthy women were included in the study. Energy expenditure and physical activity level were assessed by metabolic Holter equipment (SenseWear Armband, SWA) which was never previously used in lean PCOS population. Food int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Some studies have reported decreased total [38][39][40] and/or limb (arms and legs) 27,33,38,[41][42][43] lean tissue mass in women with PCOS versus controls. Other studies showed no differences in total [44][45][46] or limb [47][48][49][50] lean tissue mass, or muscle strength [51][52][53] between groups. To complicate matters, there is even evidence to support increased total 45,54,55 or limb 27,48 lean tissue mass, or muscle strength in women with PCOS versus controls.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Some studies have reported decreased total [38][39][40] and/or limb (arms and legs) 27,33,38,[41][42][43] lean tissue mass in women with PCOS versus controls. Other studies showed no differences in total [44][45][46] or limb [47][48][49][50] lean tissue mass, or muscle strength [51][52][53] between groups. To complicate matters, there is even evidence to support increased total 45,54,55 or limb 27,48 lean tissue mass, or muscle strength in women with PCOS versus controls.…”
Section: Introductionmentioning
confidence: 93%
“…Other studies showed no differences in total [44][45][46] or limb [47][48][49][50] lean tissue mass, or muscle strength [51][52][53] between groups. To complicate matters, there is even evidence to support increased total 45,54,55 or limb 27,48 lean tissue mass, or muscle strength in women with PCOS versus controls. 51,56 The conflicting reports may stem from small sample sizes of the individual trials, which have limited their statistical power to capture differences in muscle outcomes.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations